2019
DOI: 10.1186/s12906-019-2663-9
|View full text |Cite
|
Sign up to set email alerts
|

The synergism of Clinacanthus nutans Lindau extracts with gemcitabine: downregulation of anti-apoptotic markers in squamous pancreatic ductal adenocarcinoma

Abstract: Background Clinacanthus nutans extracts have been consumed by the cancer patients with the hope that the extracts can kill cancers more effectively than conventional chemotherapies. Our previous study reported its anti-inflammatory effects were caused by inhibiting Toll-like Receptor-4 (TLR-4) activation. However, we are unsure of its anticancer effect, and its interaction with existing chemotherapy. Methods We investigated the anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…It has been found that application of C. nutans alone or combined with gemcitabine exhibited anti-proliferative effects on pancreatic cancer cells. The summary of this combinatory therapy is the upregulation of Bax and downregulation of Bcl-2, cIAP-2, and XIAP in human pancreatic cancer cells [ 98 ].…”
Section: Classification Of Nutraceuticals Based On Modes Of Actionmentioning
confidence: 99%
“…It has been found that application of C. nutans alone or combined with gemcitabine exhibited anti-proliferative effects on pancreatic cancer cells. The summary of this combinatory therapy is the upregulation of Bax and downregulation of Bcl-2, cIAP-2, and XIAP in human pancreatic cancer cells [ 98 ].…”
Section: Classification Of Nutraceuticals Based On Modes Of Actionmentioning
confidence: 99%
“…Bcl-2 is an anti-apoptotic marker, and downregulation of Bcl-2 may promote the production of pro-apoptotic proteins (37). For example, increased Bax levels can lead to apoptotic cell death (38). Of TGF-β1 and Bax expression levels were upregulated in groups exposed to PM 2.5 .…”
Section: Discussionmentioning
confidence: 99%
“…Among all cancer cell lines, AsPC1, BxPC3, and SW1990 pancreatic ductal adenocarcinoma (PDAC) cell lines were most sensitive to nonpolar stem extracts (SN). Addition of SN extract can reduce the dosage of gemcitabine with the same effect and can potentiate the killing activity of gemcitabine to PDAC by apoptosis through upregulation of Bax, as well as downregulation of bcl-2, cIAP-2, and XIAP levels in SW1990 and BxPC3 cells independent of the TRAIL-4 expression [ 40 ].…”
Section: Anticancer Activity Of C Nutans (Cn) Extract Combined With Current Anticancer Drugmentioning
confidence: 99%